1993
DOI: 10.1159/000276353
|View full text |Cite
|
Sign up to set email alerts
|

Dumbbell-Shaped Schwannoma of the Jugular Foramen

Abstract: A 49-year-old male patient with schwannoma of the jugular foramen is described. T1-weighted magnetic resonance imaging with gadolinium showed an enhanced dumbbell-shaped mass with its smaller part occupying the left cerebellopontine angle and its larger part in left parapharyngeal space. The mass was totally removed with a left mastoidectomy and suboccipital craniotomy. The dura mater was closed with anterior lamina of the rectus sheath, and the large defect of the neck was obliterated with free rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Recently, Samii et al [14] reported a large series of 16 cases of jugular foramen schwannoma in which five tumors belonged to the dumbbell-shaped tumor category. However, only a small number of dumbbell-shaped jugular foramen schwannomas has been reported [7,8,[11][12][13][14][15]. These cases are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Samii et al [14] reported a large series of 16 cases of jugular foramen schwannoma in which five tumors belonged to the dumbbell-shaped tumor category. However, only a small number of dumbbell-shaped jugular foramen schwannomas has been reported [7,8,[11][12][13][14][15]. These cases are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Many surgical approaches to access the DSJFSs have been described (Pellet et al, 1988, Tan et al, 1990, Nibu et al, 1993, Samii et al, 1995, Takahashi et al, 1997, Gilsbach et al, 1998, Spinnato et al, 1998, Kadri and Al-Mefty, 2004, Oghalai et al, 2004, Van Calenbergh et al, 2004, Wilson et al, 2005, Sanna et al, 2006, Bruneau and George, 2008, Bulsara et al, 2008, Song et al, 2008, Chibbaro et al, 2009, Cho et al, 2009, Fukuda et al, 2009, Ichimura et al, 2009, Mazzoni, 2009), but no approach was reported for triple DSJFSs. We employed a one-stage craniocervical approach to remove triple DSJFSs, which consisted of a postauricular C-shaped incision, partial mastoidectomy, lateral suboccipital craniotomy and neck dissection, permitting exposure and opening the jugular foramen from below by following the jugular vein and from above via a lateral suboccipital approach.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Dumbbell-shaped jugular foramen schwannomas (DSJFSs) with intra and extracranial extension through enlarged jugular foramen are even rarer, and only about 130 such cases have been reported in the literature (Crumley and Wilson, 1984, Kaye et al, 1984, Shearman et al, 1986, Matsushima et al, 1989, Nibu et al, 1993, Samii et al, 1995, Takahashi et al, 1997, Spinnato et al, 1998, Yoo et al, 1999, Carvalho et al, 2000, Cokkeser et al, 2000, Lee et al, 2001, Sarma et al, 2002, Kadri and Al-Mefty, 2004, Mao et al, 2004, Oghalai et al, 2004, Wilson et al, 2005, Sanna et al, 2006, Bakar, 2008, Bulsara et al, 2008, Chibbaro et al, 2009, Cho et al, 2009, Fukuda et al, 2009, Ichimura et al, 2009, Mazzoni, 2009. DSJFS with a high cervical extension was first classified as triple DSJFS by Bulsara and colleagues (Bulsara et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation